Soluble extracts from carioca beans (Phaseolus vulgaris L.) affect the gut microbiota and iron related brush border membrane protein expression in vivo (Gallus gallus). (September 2019) - Dias, Desirrê Morais; Kolba, Nikolai; Hart, Jon J.; Ma, Michelle; Sha, Sybil T.; Lakshmanan, Naveena; Nutti, Marilia Regini; Martino, Hércia Stampini Duarte; Glahn, Raymond P.; Tako, Elad
Abstract: The effect of soluble extracts with putative prebiotic ability extracted from various bean varieties on the intestinal brush border membrane (BBM) iron related proteins, and intestinal bacterial populations were evaluated using the Gallus gallus model and by the intra-amniotic administration procedure. Eight treatment groups [(non-injected; 18 MΩ H2 O; 40 mg/mL Inulin; 50 mg/mL BRS Perola (carioca standard); 50 mg/mL BRS Cometa (carioca, Fe biofortified); 50 mg/mL BRS Esteio (black, standard); 50 mg/mL SMN 39 (black, Fe biofortified); 50 mg/mL BRS Artico (white, standard)] were utilized. Tested groups reduced the relative abundance of Clostridium and E. coli compared to the Inulin group (positive control) and they did not affect the relative abundance of Bifidobacterium and Lactobacillus compared to the negative control (18MΩ H2 O). The relative expression of zinc transporter 1, ferroportin and amino peptidase were up-regulated in the BRS Cometa group (Fe-biofortified carioca beans). Results suggest that soluble extracts from carioca beans may improve the iron bioavailability by affecting intestinal bacterial populations, and BBM functionality. Graphical abstract: Unlabelled Image Highlights: Prebiotics from carioca beans increased the abundance of beneficial bacteria. Prebiotics from carioca beans limited the amount of potentially pathogenic bacteria. Prebiotics from carioca beans improved the intestinal function. Prebiotics from carioca beans may contribute to the Fe (and zinc) transport.